2009
DOI: 10.1007/s00125-009-1462-0
|View full text |Cite
|
Sign up to set email alerts
|

Leptin prevents the metabolic effects of adiponectin in L6 myotubes

Abstract: Aims/hypothesis Adiponectin and leptin are negatively and positively correlated with human obesity respectively, and have both been shown to regulate energy metabolism in skeletal muscle. However, little is known about their signalling and functional crosstalk. Here we investigated the effects of leptin on metabolic actions of (1) globular adiponectin (gAd) and (2) full-length adiponectin (fAd) in L6 cells. Methods Glucose uptake was measured upon gAd and fAd treatment after incubation with different doses (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…Although chronic leptin treatment in rodents was shown to increase AMPK expression and activation (47), others did not detect significant changes in the expression of mitochondrial genes in response to leptin treatment compared with pair-fed mice (48). Furthermore, whereas leptin-mediated activation of AMPK was demonstrated in H9C2 cardiomyoblasts (49), others have reported that leptin attenuates AMPK activation induced by globular or full-length adiponectin in L6 myotubes (50). Thus, whereas adiponectin has consistently been shown to activate AMPK, the effects of leptin are more obscure and may depend on additional not-yet-identified coactivators.…”
Section: Discussionmentioning
confidence: 99%
“…Although chronic leptin treatment in rodents was shown to increase AMPK expression and activation (47), others did not detect significant changes in the expression of mitochondrial genes in response to leptin treatment compared with pair-fed mice (48). Furthermore, whereas leptin-mediated activation of AMPK was demonstrated in H9C2 cardiomyoblasts (49), others have reported that leptin attenuates AMPK activation induced by globular or full-length adiponectin in L6 myotubes (50). Thus, whereas adiponectin has consistently been shown to activate AMPK, the effects of leptin are more obscure and may depend on additional not-yet-identified coactivators.…”
Section: Discussionmentioning
confidence: 99%
“…selective up-regulation of CD36 protein abundance by CM as well as PA. Heat-inactivation of CM prevented this effect thus indicating that possible causative agents are protein factors. Several factors were already described to up-regulate CD36 in different cell types such as interleukin-4 in monocytes (Yesner et al, 1996), and adiponectin in L6 myotubes (Fang et al, 2009). Another factor potentially involved in up-regulating CD36 is thrombospondin-1 (TSP1).…”
Section: Discussionmentioning
confidence: 99%
“…Cell based in vitro studies show adiponectin can increase both basal and insulin-stimulated glucose uptake by promoting GLUT4 translocation to the cell membrane (Ceddia et al, 2005; Fang et al, 2005, 2009; Mao et al, 2006a) and increase fatty acid uptake and oxidation (Tomas et al, 2002; Yoon et al, 2006) through the activation of AMPK, p38-MAPK, and PPARα pathways (Yamauchi et al, 2002, 2003b; Yoon et al, 2006). Animal model studies in vivo correlate well with these observations as systemic infusion, adenoviral-based delivery or genetic overexpression of adiponectin can successfully correct high-fat diet-induced insulin resistance in skeletal muscle and decrease serum TG and FFA levels (Yamauchi et al, 2001, 2003c; Maeda et al, 2002; Combs et al, 2004).…”
Section: Adiponectin Physiology and Evidence For Contribution Of Endomentioning
confidence: 99%